3(c-5)+5=2+c-12

Simple and best practice solution for 3(c-5)+5=2+c-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(c-5)+5=2+c-12 equation:


Simplifying
3(c + -5) + 5 = 2 + c + -12

Reorder the terms:
3(-5 + c) + 5 = 2 + c + -12
(-5 * 3 + c * 3) + 5 = 2 + c + -12
(-15 + 3c) + 5 = 2 + c + -12

Reorder the terms:
-15 + 5 + 3c = 2 + c + -12

Combine like terms: -15 + 5 = -10
-10 + 3c = 2 + c + -12

Reorder the terms:
-10 + 3c = 2 + -12 + c

Combine like terms: 2 + -12 = -10
-10 + 3c = -10 + c

Add '10' to each side of the equation.
-10 + 10 + 3c = -10 + 10 + c

Combine like terms: -10 + 10 = 0
0 + 3c = -10 + 10 + c
3c = -10 + 10 + c

Combine like terms: -10 + 10 = 0
3c = 0 + c
3c = c

Solving
3c = c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-1c' to each side of the equation.
3c + -1c = c + -1c

Combine like terms: 3c + -1c = 2c
2c = c + -1c

Combine like terms: c + -1c = 0
2c = 0

Divide each side by '2'.
c = 0

Simplifying
c = 0

See similar equations:

| 3(1-10x)= | | -8(2-7p)=-16-8p | | 90-9x=-70-x | | 6v-32=2(v-8) | | x+x-3002=7878 | | x-2+9k+3= | | (Y+8)(y+3)=0 | | X^4-3x^2-6=0 | | 145=216-u | | 8-3h-6= | | 3m+1-m=-7+m-1+1 | | -10k=250 | | -3x-18=7(x+6) | | -8k+9k= | | 85=7x-5(4x-4) | | y=16x+260 | | -3x+12=-3(2x+2) | | -5x+7(x-3)=8x-9 | | 2x+-7=66 | | -7(3x-4)+7=-21x+35 | | -47=x-67 | | 3+6x=54 | | -x^2-9n-18=0 | | -3x+12=-3(2y+2) | | -14x-8=-7x-12 | | 7x+5(-2x+3)=-3 | | -2(5p-1)-5p=-40-8p | | -4(x-2)=x+-7 | | 10+-1z=0 | | 3(x-9)=5x-27 | | N+5=-3-9 | | 120-12=4-14 |

Equations solver categories